UNDERSTANDING ETHNIC IDENTITY IN THE CONTEXT OF INTERNAL MIGRATION: A CASE STUDY OF UNIVERSITY STUDENTS OF ETHNIC MINORITY ORIGINS IN URBAN BANGLADESH - Chaklader, Maidul Alam (PEOPLE: International Journal of Social Sciences, 2019)
Although much scholarly attention has been given to the historical and contemporary struggles of ethnic minority communities in Bangladesh especially related to the politics of indigeneity, this study specifically seeks to obtain a holistic understanding of the process of renegotiation and maintenance of ethnic identity as experienced by university students of ethnic minority origins in Bangladesh who have migrated from their ancestral home to urban centers. An ethnographic approach based on key informant interviews and focus groups was employed to collect qualitative data. Findings suggest that the notion of ethnic identity is not static; rather it is complex and dynamic. Although the sense of belonging to a distinct ethnic group is very important to all study participants whenever issues affecting all ethnic minorities in Bangladesh came up by dissolving inter-ethnic boundaries, participants constructed a rather homogenous ethnic identity primarily underpinned by their historical and contemporary marginal status. It is also found that ethnic migrant students with higher levels of previous ethnic involvement better maintain their ethnic identity compared to students with less previous group involvement. By revealing the importance to consider agentic forces, this finding contradicts with social identity theory which has traditionally undermined individual’s agency. Earlier studies have shown that ethnic students with higher previous ethnic involvement completely replace their previous social support network by creating a new one in the new environment. However, participants in this study simultaneously retained and accessed both their old and new social support networks depending on situational demands and opportunities. Findings also indicate that ethnic students who felt negatively about their ethnic group in the new environment showed lower self-esteem and increased alienation from their ethnic group. Relevant policy implications and future research directions have been outlined based on the study findings and discussion.